พฤติกรรมการจัดการตนเองและปัจจัยที่เกี่ยวข้องในผู้สูงอายุที่มีภาวะต่อมลูกหมากโต - สุพรรณษา กลิ่นกล่อม (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Benign prostatic hyperplasia (BPH) is a chronic disease that affecting daily life and quality of life of older people. Appropriate self-management is one way to mitigate and reduce its impacts. This study aimed to examine the relationship between self-management behaviors and factors including knowledge on disease and self-management practices, self-efficacy regarding self-management and social support. Participants were people aged 60 years or over and diagnosed BPH, not having surgery and attending urological clinics at Surat Thani, Maharaj Nakhon Si Thammarat, Trang and Hatyai hospitals (n = 90). Data were collected by using a demographic data record form, a self-management behavior scale, a knowledge scale, a self-efficacy scale and a social support scale. All instruments had been tested for validity and reliability. Data were analyzed using descriptive statistics, Spearman rank correlation and Pearson product moment correlation. The results showed that: 1. The score for overall self-management behaviors and the dimension of role and emotional management were at a high level, whereas the score for the dimension of medical management was at a moderate level. 2. The score of related factors including knowledge on disease and self-management practices, self-efficacy regarding self–management and social support were at high level.